Dynamic multi-granularity semantic representations for navigation facility services. (2016) - Mondo, Géraldine Del; Mainguenaud, Michel
The main purpose of this article is to tackle the management of alphanumeric data provided to end users in navigation facility services. We propose, via a top down and interpreted approach, to define a data model. The aim is to take into account the spatial relevance of alphanumeric attributes using a logical spatial representation (not using a cartographical representation). Based on a conventional database model extended with links to model relationships between alphanumeric attributes and spatial semantics, this model provides the management of several levels of abstraction (granularity levels). We describe a data manipulation operator to zoom into a deeper abstraction level and we define rules to build the data model associated with the results of this operator.